Nuclear envelope and genome interactions in cell fate - Talamas, Jessica A.; Capelson, Maya (Frontiers in Genetics, 2015)
The eukaryotic cell nucleus houses an organism’s genome and is the location within the cell, where all signaling-induced and development-driven gene expression programs are ultimately specified. The genome is enclosed and separated from the cytoplasm by the nuclear envelope (NE), a double-lipid membrane bilayer, which contains a large variety of trans-membrane and associated protein complexes. In recent years, research regarding multiple aspects of the cell nucleus points to a highly dynamic and coordinated concert of efforts between chromatin and the NE in regulation of gene expression. Details of how this concert is orchestrated and how it directs cell differentiation and disease are coming to light at a rapid pace. Here we review existing and emerging concepts of how interactions between the genome and the NE may contribute to tissue-specific gene expression programs to determine cell fate.